Macroeconomic Trends and Features of Regional Economy Development in the 21st Century - Litvinenko, Inna L.; Syzdykova, Zhibek S.; Novoselov, Sergey N.; Novoselova, Natalya N.; Gureva, Maria A.; Tupchienko, Vitaly A. (International Journal of Economics and Financial Issues, 2016)
At present there is a tendency to the general Russian economic crisis and the disintegration of the economic space and various basic conditions of separate regions, which are focused on the market in the development of regions. Today the regions with a high concentration of stagnating and converting industries and the incomplete investment programs of development, the regions, which are directly dependent from raw material and food supply and also the districts, which have an intense ecological situation, where it is necessary to terminate the functioning of a number of the ecological harmful enterprises and to make measures for the social protection of the population of this region, are under more severe conditions. A number of the regions of the Far East, Siberia, the Urals and the Center are referred to these districts. The fundamentalization of Russia's integral economic space directly depends on a capital market by forming the system of joint stock companies, stock exchanges, commercial banks and funds for commodity and raw material resources. Commercial firms and entrepreneurs have a considerable potential in the questions about supplying the enterprises of various regions with material and technical resources, and the population with food. Keywords: macroeconomics, Gross Domestic Product (GDP), happiness index, consumer demand, capital, investment activity, integration, import substitution, capital market JEL Classifications: E01, O11, O20, R11, R13